2004
DOI: 10.1039/b403753g
|View full text |Cite
|
Sign up to set email alerts
|

A general one-pot process leading to highly functionalised ordered mesoporous silica films

Abstract: Various organic moieties are homogeneously introduced in high quantities into mesostructured porous silica films through a general co-condensation process, which influences the self-assembly mechanism, depending on the physico-chemical properties of each function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 12 publications
3
86
0
1
Order By: Relevance
“…Cagnol et al [9] reported a general route for the direct synthesis of functionalized CTAB-templated silica thin films, using eleven organotrialkoxysilanes, differing by their physical-chemical properties. Brinkers group [10] used the one-pot method to prepared ordered aminopropyl functionalized silica thin films as pH sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Cagnol et al [9] reported a general route for the direct synthesis of functionalized CTAB-templated silica thin films, using eleven organotrialkoxysilanes, differing by their physical-chemical properties. Brinkers group [10] used the one-pot method to prepared ordered aminopropyl functionalized silica thin films as pH sensors.…”
Section: Introductionmentioning
confidence: 99%
“…It also allows the use of extraction as the only method for surfactant removal, as calcination could destroy organic compounds. After pioneering works of the groups of Mann and co-workers [33] and MacQuarrie [34], many different organically modified mesoporous silicas have been prepared by co-condensation, including those modified with alkyl, thiol, vinyl/allyl [35], amino, cyano/isocyano [36], alkoxy [37], organophosphine, and aromatic groups [38]. Periodic mesoporous organosilicas (PMOs) are materials with modified matrices but preserved organized pore system and narrow pore size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The mesoporous structure is particularly useful for sensing applications, where short diffusion times and easy access of the target analyte towards the sensing species are required. 3 Regarding sensors, mesoporous materials have so far been mainly applied to electrodes 4,5 and to quartz-crystalmicrobalance (QCM) 6,7 sensors.…”
Section: Introductionmentioning
confidence: 99%